Polska Partia Socjalistyczna w powiecie częstochowskim w latach 1945-1948 - SZCZYPKA , Andrzej (Historia i Świat, 2014)
During the first three months after the liberation of the Częstochowa district by the Red Army the structures of the Polish Socialist Party were rebuilt. Its completion was achieved by the time the first town and district congress of PSP took place on 29th April 1945. . The function of the provisional town and district president of PSP was entrusted to Jan Kaźmierczak.The socialists from Częstochowa assumed several important positions in the civil service,e.g. Bronisław Federak became the vice president of Częstochowa and Ferdynand Szmidla was appointed the president of the Municipal National Council. Two parties competed for the influence in the working class community – Polish Workers’ Party and Polish Socialist Party. Due to this political competition some conflicts between these parties arose. One of them became especially conspicu-ous after the comunists’ loss in the elections to the works councils. However, the mutual antagonism between the two parties abated in connection with the referendum and elections to the Legislative Sejm as both parties cooperated with each other in the propaganda actions. After the communists’ win in the Legislative Sejm elections, they started the stage of assuming control over PSP. Their methods included organization of meetings for the activists of both parties during which those PSP members who were against the communists’ politics were eliminated, often with the help of Secret Service executing frequent arrests. The main goal of all these intimi-dating actions was to weaken PSP by forcing the socialists to join the Polish Workers’ Party. The decision concerning such a strategy was made during the meeting of the Political Bureau of the Central Committee of the Polish Workers’ Party on 6th March 1948 and it was fulfilled in the middle of December 1948 during the Unification Congress when The Polish United Workers’ Party was established.